Ukusebenza nethongo (Working with Spirit): the role of sangoma in contemporary South Africa - Wreford, Jo Thobeka (Social Anthropology, 2015)
This thesis represents a typically boundary-crossing ethnographic experience and an unconventional anthropological study, its fieldwork grounded in the author's personal experience of ukuthwasa - initiation, training and graduation - to become a sangoma, a practitioner of traditional African medicine, in contemporary South Africa. The study is contextualized within the contemporary health dispensation in South Africa in which two major paradigms, traditional African healing, considered within the spiritual environment of sangoma, and biomedicine, operate at best in parallel, but more often at odds with one another. Given the unprecedented challenge of the HIV/AIDS pandemic in the country, the thesis suggests that this situation is unhelpful and proposes first, that a more collaborative relationship between medical sectors is vital. Secondly, the thesis suggests that anthropologists can play an important role in achieving an improved dialogue, by producing research grounded in the spiritual aetiology of sangoma but comprehensible to academic science and applicable within collaborative medical interventions. The thesis introduces 'sacred pragmatics' to embody the disarmingly matter-of-fact quality of sangoma healing which is nevertheless always underpinned by the authority of ancestral spirit solicited in terms that are reverent. Ancestral authority in sangoma is advanced as a credible near equivalent to Jung's 'collective unconscious', and the contemporary phenomenon of white sangoma is proposed as a potential source of social and political healing. In the light of the spiritual foundation of sangoma, the absence of spirituality in biomedicine is discussed and its effect on relationships between medical sectors analysed. The umbilical and ambiguous connection of sangoma and witchcraft is acknowledged, a relationship theorised as having transformative potential within kin and community. The theoretical arguments are set against the evidence of fieldwork which is characterised as experiential and described reflexively. The thesis constitutes a start in what the author hopes will develop into an ongoing conversation between traditional African healing, academe and biomedicine in South Africa.